Doktrin Roh Kudus dan Kehidupan Bergereja: Kajian Sistematika Konstruktif Atas Persoalan,Ketegangan,dan Relevansinya di Era Modern - Muliku, Cristofan (DELAHA: Journal of Theological Sciences, 2025)
The doctrine of the Holy Spirit is a central component of Christian theology, yet in contemporary church life it often suffers from a diminished role and lack of holistic application. Today’s churches face various pneumatological issues, including the reduction of the Holy Spirit to a mystical force, imbalance between doctrinal formulation and spiritual experience, and the lack of integration between the Spirit’s work and communal life. This study aims to evaluate and reconstruct the doctrine of the Holy Spirit systematically and constructively, making it more contextual and relevant for the modern church. Using a qualitative theological method through library research, this study employs both systematic theology and constructive theology approaches. It critically engages with the theological insights of Joas Adiprasetya, John Frame, Wolfhart Pannenberg, Vera Loupatty, and Wayne Grudem. The analysis reveals tensions between dogmatic and charismatic approaches, as well as a detachment of the Spirit’s work from the Trinitarian framework—factors that contribute to the weakened pneumatological awareness in the church. As a constructive response, this study proposes a renewed formulation of the Holy Spirit doctrine that emphasizes the Spirit’s role within Trinitarian and communal relationships, as the sustainer of church life and agent of God’s mission, and as a bridge between doctrine, spirituality, and social praxis. It also underlines the need for a contextual and pastoral pneumatological language. Thus, the doctrine of the Holy Spirit can be lived out as a dynamic, reflective, and transformative reality for the church in today’s world.